Endodontic Pain Diagnosis, Causes, Prevention and Treatment - Rosenberg, Paul A. (Springer Berlin Heidelberg : Imprint: Springer, 2014)
Endodontic pain is a complex symptom that often drives a patient to a dentist in search of relief. In these circumstances, the patient is likely to pose a range of questions: Can you relieve my pain? Will the treatment be painful? How will I feel later? The answers to such questions often form the basis of the patient's assessment of the dentist. The combination of pain and a negative dental experience has physical and psychological sequelae for the patient that may last long after treatment.  This book is a concise, well-structured guide to the assessment and treatment of patients who present with endodontic pain, in which step-by-step descriptions are complemented by informative images and flow charts. The advantages, disadvantages, and significance of specific diagnostic and treatment procedures are clearly described, as is a pharmacotherapeutic approach to the prevention and treatment of pain. In addition, the causes and biological basis of endodontic pain are explained and guidance is provided on further strategies for pain prevention. The crisp narrative, efficient design, and visual detail are notable features of this book that will make it an ideal chairside resource for the clinician and a dependable reference for the student.